RETRACTED: A Humanistic Philosophical Analysis on Women Existence in The Fiqh of Syafi'i - Nur, Iffatin (KALAM, 2015)
This article has besn retracted because it was published in another journal. This article can be found at ULUMUNA: Journal of Islamic Studies, Volume 19, No. 1 of 2015. https://ulumuna.or.id/index.php/ujis/article/view/223